Investigating Pre-Service Biology Teachers' Diagnostic Competences: Relationships between Professional Knowledge, Diagnostic Activities, and Diagnostic Accuracy - Maria Kramer; Christian Förtsch; William J. Boone; Tina Seidel; Birgit J. Neuhaus (MDPI AG, 2021)
Teachers' diagnostic competences are essential with respect to student achievement, classroom assessment, and instructional quality. Important components of diagnostic competences are teachers' professional knowledge including content knowledge (CK), pedagogical knowledge (PK), and pedagogical content knowledge (PCK), their diagnostic activities as a specification of situation-specific skills, and diagnostic accuracy. Accuracy is determined by comparing a teacher's observation of classroom incidents with subject-specific challenges to be identified from scripted instructional situations. To approximate diagnostic situations close to real-life, the assessment of science teachers' diagnostic competences requires a situated context that was provided through videotaped classroom situations in this study. We investigated the relationship between professional knowledge (PCK, CK, PK) of 186 pre-service biology teachers, their diagnostic activities, and diagnostic accuracy measured with the video-based assessment tool DiKoBi Assess. Results of path analyses utilizing Rasch measures showed that both PCK and PK were statistically significantly related to pre-service teachers' diagnostic activities. Additionally, biology teachers' PCK was positively related to diagnostic accuracy. Considering higher effect sizes of PCK compared to PK, the findings support previous findings indicating the importance of PCK, thus demonstrating its importance in the context of subject-specific diagnosis as well.